2013
DOI: 10.1007/s00134-013-3195-2
|View full text |Cite
|
Sign up to set email alerts
|

Arterial blood pressure changes induced by acceleration during mobile intensive care unit patient transport are not patient related: beware of misinterpretation

Abstract: Arterial blood pressure changes induced by acceleration during mobile intensive care unit patient transport are not patient related Droogh,

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…In conclusion, being airborne aboard a helicopter had minimal and clinically irrelevant impact on the physiological variables, compared with the reference period prior to take-off. Noteworthy, a simulation study showed that variations in invasive blood pressure readings during accelerations or decelerations can be artifacts resulting from inevitable physical phenomena [ 5 ]. The time courses of physiological variables and absence of complications suggest that helicopter transport can contribute to safe inter-hospital transfers of ventilated COVID-19 patients.…”
mentioning
confidence: 99%
“…In conclusion, being airborne aboard a helicopter had minimal and clinically irrelevant impact on the physiological variables, compared with the reference period prior to take-off. Noteworthy, a simulation study showed that variations in invasive blood pressure readings during accelerations or decelerations can be artifacts resulting from inevitable physical phenomena [ 5 ]. The time courses of physiological variables and absence of complications suggest that helicopter transport can contribute to safe inter-hospital transfers of ventilated COVID-19 patients.…”
mentioning
confidence: 99%